ANALISA HASIL AUDIT PEMERINTAH TERHADAP TINGKAT KORUPSI PEMERINTAHAN PROVINSI JAWA TENGAH - Albab, Ahmad Ulil; Nur savitri, Anava Salsa; Anwar, Saiful (Accounting Global Journal, 2019)
This research aims to analyze the influence of goverment auditing results such as audit opinion, audit finding, audit retrification on the level of corruption in Central Java Province. This research uses purposive sampling and the research uses secondary data from audit results of State audit board of indonesia (BPK-RI) and data total corruption from Komisi Pemberantasan Korupsi (KPK) and Indonesian Corruption Watch (ICW). The population in this study is all districts and cities in central Java Province.The results of this study showed that audit opinion has negative effect on corruptin level, and that partials audit finding has negative effect and significant on corruption level and audit retrification has positive effect and sifnificant on corruptin level. Simultaneously, these variables have significant influence on corruption level.